Metabolic regulation of sirtuins upon fasting and the implication for cancer - Zhu, Yueming (Curr Opin Oncol, 2013)
PURPOSE OF REVIEW: The purpose of this review is to highlight recent studies on mammalian sirtuins that coordinately regulate cellular metabolic homeostasis upon fasting and to summarize the beneficial effects of fasting on carcinogenesis and cancer therapy. RECENT FINDINGS: Recent studies have demonstrated that fasting may protect normal cells and mice from the metabolic conditions that are harmful as well as decrease the incidence of carcinogenesis. Fasting could also slow the tumor growth and augment the efficacy of certain systemic agents/chemotherapy drugs in various cancers. The mechanism behind this proposed idea may be due to, at least in some part, the metabolic regulation by sirtuin family proteins whose functions are involved in specific aspects of longevity, stress response and metabolism. Sirtuins, particularly SIRT1 and SIRT3, can be activated by fasting and further exhibit their effects in insulin response, antioxidant defense, and glycolysis. Therefore, sirtuins may have anticancer effects by shifting metabolism to a less proliferative cell phenotype as well as less prone to oxidative stress attack. SUMMARY: The in-depth understanding of the essential role of sirtuins in the fasting process may have significant implications in developing a new metabolic diagram of cancer prevention or treatment.